At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

6(x- 4)-8=6(x-2)+4x



Sagot :

Answer:

x = -5

Step-by-step explanation:

6(x - 4) - 8 = 6(x - 2) + 4x

=> 6x - 24 - 8 = 6x - 12 + 4x

=> -24 - 8 = -12 + 4x

=> -32 = -12 + 4x

=> -20 = 4x

=> x = -5

Therefore, x = -5 is our answer.

Hoped this helped.

Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.